UNDERSTANDING WORKPLACE INCIVILITY: THE ROLE OF GENDER, ETHICAL LEADERSHIP, PERSONAL CONTROL, AND RELIGIOSITY - Nurul Khair bt Ishak,; Nur Aulia Fahada binti Misaridin,; Nur Yani bt Che Hussin,; Raja Nurul Hafizah bt Raja Ismail, (Journal of Islamic, Social, Economics and Development, 2023)
Workplace incivility is not always defined by shouting and other rude conduct. It may be characterized as a low intensity unethical action with an unknown aim to harm the target in violation of workplace rules for mutual respect. Workplace incivility has long been debated. It has a detrimental impact on work outcomes such as negatively impacting workplace relationships, engaging in knowledge-concealing behaviours such as acting dumb or evasive hiding, and being less involved, which may lower employee job standards of quality. Therefore this conceptual paper will investigate the determinants of workplace incivility including gender, ethical leadership, personal control and religiosity. This analysis has revealed that workplace incivility represents a notable problem that has adverse effects on both individuals within the workforce and the overall functioning of organizations.